“They are stealing the state”. Commoning and the Gilets Jaunes in France. - Susser, Ida (Routledge, 2021)
In the context of the political polarization in Europe following the 2008 recession, the extreme right has been energized, while new progressive parties have also been formed. Analysts have described changing global relationships and the impact of financialization, but there is a need to investigate the social transformation in the practice of democracy that may be occurring. Is there a new political bloc or a working class with consciousness or agency emerging? This chapter analyzes the Gilets Jaunes protests in the streets of Paris, France, in 2018/2019, and discusses whether they might be understood as “commoning.” Demonstrators included all generations from youths to middle-aged people and pensioners, many from the provinces and the urban peripheries of France. The chapter asks where such protests fit in terms of alternative democratic processes in this polarizing moment. Analysis of the Gilets Jaunes views of the state and their efforts to build community suggests these forms of contestation may be transforming urban ethics and reconfiguring democracy.
Keywords: Protestbewegung; Demonstration; Gemeinwesen; Zivilgesellschaft; Bevölkerungsgruppe; Demokratieverständnis; Alternativbewegung; Ethik; Gemeinwesen; Transformation; Gelbwesten